Into the Emptiness. Strategies for Questioning Reality from the Recent Galician Poetry - Marante Arias, Antía (Madrygal. Revista de Estudios Gallegos, 2015)
Through the analysis of the collection of poems Fase de trema by Lorena Souto (Espiral Maior, 2012) and Cero by Oriana Méndez (Galaxia, 2011), a reading of these poems will be suggested as proposals that trough the use of the “Madness metaphor” seek a specific intertextual dialogue in order to boost a deconstructive speech –in Derrida’s terms– about reality questioning in order to bring new positions from the literary.